An unusual presentation of an uncommon lymphoma, hepatosplenic T-cell lymphoma. Issue 1 (2nd January 2019) - Amin, Sima; Findeis, Sarah K.; Whiteley, Andrew; Krause, John R.
Abstract: Hepatosplenic T-cell lymphoma (HSTCL) is a rare T-cell lymphoma, primarily characterized by extranodal distribution of the malignant cells with intrasinusoidal infiltration of the liver, spleen, and bone marrow, which is associated with a poor outcome. We describe a unique case of a 47-year-old woman with a clinical presentation of headaches, fevers, elevated liver function tests, and hepatosplenomegaly. A liver biopsy revealed a striking hepatic intrasinusoidal infiltrate of lymphocytes. These were confirmed to be T cells by immunohistochemical stains (CD8 +, CD4 −, CD3 +, CD20 − ). Molecular studies demonstrated a T-cell gamma receptor gene rearrangement. Clinically, the patient appeared to improve without therapeutic intervention; however, because of the pathologic diagnosis, the patient was initiated on chemotherapy and ultimately underwent a bone marrow transplant.